Physicochemical characteristic of tea infusion yoghurt inoculated with Caspian Sea Yoghurt - Shinta Maharani,; Nanda Anggita Sari,; Anita Rahayu,; Prawira-Atmaja, M Iqbal; A, Ana (Penerbit Universiti Kebangsaan Malaysia, 2020)
Application inoculum from Caspian Sea Yoghurt to produce yoghurt containing tea infusion have not been developed thoroughly, until recently. This study aimed to determine the physicochemical characteristic and sensory evaluation of tea infusion yoghurt inoculated with Caspian Sea Yoghurt. Green, white, and black tea infusion were added to UHT milk inoculated with Caspian Sea Yoghurt inoculum and incubated at 30 °C for 12 h. The yoghurt was analyzed at 0, 6, and 12 h of fermentation including pH, acidity, viscosity, colour (L, a*, b*), total polyphenol, and sensory evaluation. The result showed additional tea infusion on manufacturing yoghurt significantly affected on pH, percentage of acidity, viscosity, and colour parameter of yoghurt. During the fermentation process, the prolonged incubation time resulted in increased acidity and viscosity, while simultaneously decreased the pH value. At the end of the fermentation (at 12 h) of yoghurt with 10% tea infusion had a lower pH and a higher percentage of acidity compared to the yoghurt control. Addition of tea infusion on yoghurt has a lower viscosity than yoghurt without tea infusion at the end of the fermentation. Additional tea infusion on yoghurt affected reduced Lightness (L*) value but increased a* and b* value. The results of the present study indicate that additional tea infusion on yoghurt inoculated with Caspian Sea Yoghurt should be considered not only in terms of physicochemical and sensory during manufacturing and storage but also functional properties to improve human health.